Questioning the Distribution of Fidyah Funds on Digital Platforms in Indonesia - Balya Nasim Ahmad; Tri Hidayati (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
The purpose of this study is to find out the authority of the institution that oversees various digital platforms for fidyah payments, the accuracy of the target recipients of fidyah, the form and value paid are in accordance with Sharia principles, and the timeliness of their distribution. This research method is a library research and also normative research that is analyzed qualitatively, descriptively, and precautionatively with the approach of Islamic Law. The results in this study are that there is a platform that is not purely an activist to accommodate fidyah distribution services the next finding regarding the target recipients is distributed which is not a theme such as the nash in verse 184 of Surah al-Baqarah, namely the poor. The conversion of the nominal form of fidyah delivery on various different platforms and the problem of the time of distributing fidyah which is still not very detailed and clearly causes the existence of gharar. With the rise of fidyah distribution platforms providing convenience for Muslims fidyah payments through platforms have a maslahah impact for Muslims, there is a need for order attention, supervision and rules on the distribution of fidyah in institutions and fidyah platforms by relevant stakeholders.